Implementasi Sistem Informasi Manajemen dalam Meningkatkan Efektivitas Layanan Administrasi Pendidikan di SMP IT Cordova Pondok Aren - Safrida Nurlaily Saadah; Suheri Mukhti; Singgih Aji Purnomo (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The rapid development of information and communication technology has brought major changes in various fields of life, in cluding in the field of education. Educational institutions are required to be able to manage administration effectively, efficiently, and integrally in order to be able to provide quality educational services. One of the efforts that can be made is to implement the Management Information System (SIM) in the management of school administration. This study uses a qualitative method with a case study approach. Data collection techniques are carried out through interviews, observations, and documentation. The research subjects consisted of school principals, heads of administration and homeroom teachers. This study aims to determine the implementation of Management Information Systems in improving the effectiveness of educational administration services at SMP IT Cordova Pondok Aren. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the implementation of the Management Information System at Cordova IT Junior High School has helped increase the effectiveness of educational administration services, especially in the management of student data, attendance, assessment, and information services to students' parents. However, in its implementation, there are still several obstacles, such as limited technological facilities and infrastructure, instability of the internet network, and uneven use of the system by all educators. Therefore, efforts are needed to develop systems, improve technology facilities, and training for educators and education personnel so that the use of Management Information Systems can run more optimally and sustainably in supporting the improvement of the quality of educational administration services.